ANALISIS KEBUTUHAN DAN PENGUATAN KOMPETENSI GURU BIMBINGAN KONSELING DI PP. DARUSSALAM BLOKAGUNG - M Rizqon Al Musafiri; Nur Hafifah; Chumeysa Yuslihati Intiha; Nur fitria Fatmawati (Jurnal At-Taujih, 2023)
Problems related to the needs of counselling guidance teachers in the education unit of PP Darussalam. The purpose of this study is to identify aspects of competence that need to be emphasised in strengthening the competence of counselling guidance teachers at PP Darussalam Blokagung Banyuwangi. This type of research uses quantitative and qualitative approaches (Mix Methode). . Data were obtained from questionnaires and interviews distributed to counselling teachers at units in PP Darussalam Blokagung ranging from SD, SMP, MTs, SMA, SMK, MA. The needs analysis of counselling teachers has 7 main points of problems (1) Teachers are still adapting to counselling materials; (2) the division of tasks between class teachers, students and counselling teachers is not appropriate; (3) counselling teachers do not come from a counselling background; (4) counselling teachers are given other subjects besides counselling; (5) counselling teachers do not have counselling certification; (6) the ratio of counselling teachers is not appropriate; (7) differences in handling between pesantren and schools. Permasalahan yang terkait dengan kebutuhan guru Bimbingan Konseling di unit pendidikan PP Darussalam. Tujuan penelitian ini yaitu Mengenali aspek kompetensi yang perlu mendapatkan penekanan dalam penguat kompetensi guru bimbingan konseling di PP Darussalam Blokagung Banyuwangi. Jenis penelitian ini menggunakan pendekatan kuantitatif dan kualitatif (Mix Methode). . Data diperoleh dari kuesioner dan wawancara yang dibagikan kepada guru BK pada unit di PP Darussalam Blokagung mulai dari SD, SMP, MTs, SMA, SMK, MA. Analisis kebutuhan guru BK memiliki 7 poin utama masalah (1) Guru masih beradaptasi dengan materi bimbingan konseling; (2) pembagian tugas antara guru kelas, kesiswaa dan guru BK yang belum sesuai; (3) guru BK bukan berasal dari latar belakang BK; (4) Guru BK diberikan mapel lain selain BK; (5) Guru BK belum memiliki sertifikasi konseling; (6)Jumlah Rasio guru BK yang belum sesuai; (7) Perbedaan penanganan antara pesantren dan sekolah.